Ali sploh še potrebujemo prevajalce? - Mezeg, Adriana (Ars et humanitas, 2023)
Given the improvement of machine translation (MT) in recent years, we often wonder if these tools could one day replace a human translator. In this paper, we present the results of a survey on the use of MT among French students at the Department of Tran-slation in Ljubljana. We then analyse the errors in MT of four texts from French into Slovene created with Google Translate and DeepL. The analysis shows that DeepL is slightly better than Google Translate, which has improved over the years, but the qua-lity of MT from French into Slovene is still not at the level of human translations, with lexical errors outweighing grammatical and stylistic errors. Most students use MT as a translation aid because they believe it will make their translations from French into Slovene better, but they do not know if they have the skills to correct them. Therefore, it is not enough to teach students to be excellent translators themselves, as we also need to focus their education on developing skills for postediting MT, since it is very likely that translators will mainly work as posteditors in the future
Keywords: DeepL; francoščina; French; Google; machine translation; popravljanje strojnih prevodov; postediting machine translation; Slovene; slovenščina; strojno prevajanje